Efficacy and safety of acupuncture treatment on primary insomnia: a randomized controlled trial - Xuan Yin; Minghui Gou; Jian Xu; Bo Dong; Ping Yin; Fernand Masquelin; Junyi Wu; Lixing Lao; Shifen Xu (2017)
The objective of this study was to evaluate the efficacy and safety of acupuncture treatment for primary insomnia.We conducted a single-center, single-blinded, and randomized controlled clinical trial. Seventy-two patients with primary insomnia were randomly assigned into two groups - the acupuncture group, who received acupuncture treatment, and the control group, who received sham acupuncture treatment. The treatment was given three times a week for four weeks. Patients were asked to wear sleep monitors and complete questionnaires every two weeks for a total of eight weeks. The primary outcome was the Insomnia Severity Index (ISI). The secondary outcomes were sleep parameters including sleep efficiency (SE), sleep awakenings (SA) and total sleep time (TST) recorded by the Actigraphy, as well as scores of the Self-Rating Anxiety Scale (SAS) and the Self-Rating Depression Scale (SDS).Compared with pretreatment baseline, patients in both groups had varying degrees of improvements in their sleep conditions. Paired t-test showed that there was a significant difference in all indicators in the acupuncture group before and after acupuncture treatment. One-way analysis of covariance adjusted for baseline scores indicated that the ISI improved dramatically in the acupuncture group at two weeks post-treatment (F = 11.3, p = 0.001), four weeks post-treatment (F = 33.6, p < 0.001), 2 weeks follow-up (F = 39.4, p < 0.001) and four weeks follow-up (F = 34.1, p < 0.001). Similar significant improvements can also be observed in the SE, TST and SDS scores. Although no differences in SA and SAS were shown between the two groups until the end of the treatment, remarkable decrements in SA and SAS were found in the acupuncture treatment group after the two-week and four-week follow-ups.Acupuncture treatment is more effective than sham acupuncture treatment in increasing insomnia patients' sleep quality and improving their psychological health.Chinese Clinical Trial Registry: Chi CTR-TRC-14004859.